Functional nanofibers and their applications - Wei, Q. (Woodhead Publishing, 2012)
"Nanofibers are a flexible material with a huge range of potential applications in areas such as technical textiles. The book summarises key trends in the processing and applications of these exciting materials."--Back cover.
Published in association with the Textile Institute.
Keywords: Textile fibers, Synthetic.; Nanostructured materials.; Nanofibers.; elektronické knihy; electronic books